IDENTIFICATION OF THE CHARACTERISTICS OF PALEOTSUNAMI DEPOSITS IN THE SUKABUMI, WEST JAVA PROVINCE - Yunsa Saputra, Eryk
Subduction zone located in the south of Java Island have the potential to repeat large underwater earthquakes that can cause a tsunami. For this reason, a paleotsunami deposit is needed to determine the tsunami pattern that has occurred on the south coast of Java. The Ciracap area was chosen to correlate the availability of paleotsunami deposits previously carried out such as in Banten, Pangandaran, and Cilacap. The research was carried out on hand drill samples with a UG-05 code of 326 cm. Characteristic identification of paleotsunami deposits was obtained by conducting laboratory analysis in the form of grain size analysis (granulometry), analysis of X-ray fluorescence (XRF) and analysis of foraminifera microfossils. The results of the analysis of the sample shows that there are two layers of paleotsunami deposited in the swale environment (a basin between two ridge). The layer is at a depth of 235 cm - 257 cm and 190 cm - 199 cm is characterized by erosional contact with the layer below it. Based on the item analysis, the Paleotsunami I deposit has a thickness of 22cm, dark gray, measuring 4,317 phi - 2,015 phi (very coarse silt - fine sand), Sorting value 1,709 phi - 2,662 phi (poorly sorted - very poorly sorted), kurtosis value 0.736 phi - 2,134 phi (symmetrical - very leptokurtic), skewness value 0.043 phi - 0.649 phi (symmetrical - very fine skewed) and bimodal frequency distribution curve. While the paleotsunami II deposit has a thickness of 9 cm, brown, measuring 2,784 phi - 4,725 phi (very coarse silt - fine sand), the sorting value is 2,526 phi - 2,810 phi (very pooly sorted), the kurtosis value is 0.712 phi - 0.896 phi (platykurtic), value of 0.017 phi - 0.488 phi (symmetrical - very fine skewed) and bimodal frequency distribution curve. XRF analysis shows the abundant substances and layers in the paleotsunami I and II layers compared to the non-candidate paleotsunami layers. The highest average value of Ca in the Paleotsunami I and II candidate layers is 102975.50 ppm and 91526.13 ppm and the average does not average 893.22 ppm and 875.34 ppm. This edition contains ingredients derived from the sea. The abundance of foraminifera in the paleotsunami I layer is very abundant, found 16 species of planktonic foraminifera and 14 species of foraminifera bentonic both intact and cracked. While the abundance of foraminifera in the paleotsunami II layer is quite abundant, 13 species of planktonic foraminifera and 8 species of bentonic foraminifera were found intact or in cracked conditions. This is the source of the tsunami sediment source comes from the sea..